Spiritual Intelligence and its Practical Importance – Insights from Oman (Global Journal of Management and Business Research, 2023)
Introduction- In a world described as pessimistic and characterized by the deterioration of moral values the opportunity to raise the bar of personal integrity and to positively contribute to the lives of others is possible when individuals choose to find their voice and help those around them to find theirs as well Bennis 2009 The challenge to discover one s unique significance by finding one s voice was often the theme of management guru Stephen R Covey who passed away in 2012 but his message and its profound importance continue to resound as an invitation to young men and women to become the best version of themselves and to help others to grow and to flourish Covey 2005